2020
DOI: 10.1055/s-0040-1715553
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Lycopene against Reperfusion Injury in Rats with Ovarian Torsion: A Biochemical and Histopathological Evaluation

Abstract: Objective The aim of our study was to evaluate the effect of two different doses of lycopene, an antioxidant, on experimentally induced ovarian ischemia/reperfusion (IR) injury in rat model. Materials and Methods Twenty-four female rats were randomly divided into four groups: sham operation (group 1), 3-hour ischemia, 3-hour reperfusion (IR) (group 2), and IR + 100 mg/kg lycopene (PO) (group 3), IR + 200 mg/kg of lycopene (group 4). The rats’ superoxide dismutase (SOD), myeloperoxidase (MPO) activities, malond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…With the occurrence of ischemia, when physiopathological conditions arise as a result of the inability to provide sustenance to the brain tissue, oxidative stress develops as a result of the restoration of blood flow to ischemic areas through physiological and iatrogenic methods 11 . The increased amount of oxygen causes an excessive amount of free oxygen radicals in tissues adapted to hypoxia, leading to additional reperfusion injuries at the site of ischemic damage 12–14 . Therefore, new approaches that will eliminate or reduce ischemia reperfusion injury in all ischemic conditions are still being investigated 12–16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the occurrence of ischemia, when physiopathological conditions arise as a result of the inability to provide sustenance to the brain tissue, oxidative stress develops as a result of the restoration of blood flow to ischemic areas through physiological and iatrogenic methods 11 . The increased amount of oxygen causes an excessive amount of free oxygen radicals in tissues adapted to hypoxia, leading to additional reperfusion injuries at the site of ischemic damage 12–14 . Therefore, new approaches that will eliminate or reduce ischemia reperfusion injury in all ischemic conditions are still being investigated 12–16 .…”
Section: Introductionmentioning
confidence: 99%
“…The increased amount of oxygen causes an excessive amount of free oxygen radicals in tissues adapted to hypoxia, leading to additional reperfusion injuries at the site of ischemic damage 12–14 . Therefore, new approaches that will eliminate or reduce ischemia reperfusion injury in all ischemic conditions are still being investigated 12–16 . Notably, phosphodiesterase (PDE) inhibitors have also been discussed in this context 16 …”
Section: Introductionmentioning
confidence: 99%
“…One portion was placed in a 10% formalin for histopathological evaluation, while the other one was preserved at -80 °C for chemical analysis. Then, 0.1 g of the tissue was homogenized in 900 µL of ice-cold phosphatebuffered saline at pH 7.4 (10% w/v) and centrifuged at 4,000 rpm for 15 min at 4 °C (Yilmaz et al 2020). The supernatants were stored at -80 °C for colorimetric assay of malondialdehyde (MDA), reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), and nitric oxide (NO) levels (Biodiagnostic, Egypt).…”
Section: Methodsmentioning
confidence: 99%
“…Ovarian specimens were fixed in 10% formalin solution for 72 h. Paraffinembedded samples (5 mm) were cut and stained with hematoxylin and eosin (H&E). All the sections (multiple sections/rat) were examined under an Olympus (Japan) light microscope (Yilmaz et al 2020). According to the histopathological evaluation system, 5 microscopic fields were examined to assess the degree of congestion, hemorrhage, edema, inflammatory cells infiltration, and follicular degeneration.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, lycopene has also been shown to improve ovarian I/R injury. One study [175] showed that at 2.5 h after ischemia (3 h), lycopene treatment (100 and 200 mg/kg, i.g.) could effectively reduce tissue congestion, hemorrhage, and polymorphonuclear leukocyte infiltration via increasing GSH and CAT and lowering MDA and MPO.…”
Section: Lycopene Attenuates Reproductive Organ I/r Injuriesmentioning
confidence: 99%